Antifungal Properties of Selected Medicinal Plants against Crop Pathogenic Fungi - Siew Ting, Ling (UNIMAS, 2022)
Crop diseases caused by crop pathogenic fungi are leading to considerable yield losses of crop. Conventional fungicides have been utilized extensively in curbing crop diseases. Considerable efforts are directed at exploring potential of plant-derived fungicides as alternative to conventional fungicides. Biodegradable plant-derived fungicides hold promise for sustainable crop protection. The present study aimed to determine the antifungal potential of selected medicinal plants to be used as a plant-derived fungicide. Sequential extraction using absolute n-hexane, ethyl acetate, and methanol was performed on Garcinia mangostana, Moringa oleifera, Clinacanthus nutans, Cymbopogon citratus, Elephantopus scaber, Pandanus amaryllifolius, Triticum aestivum, Polygala paniculata and Tridax procumbens to obtain crude extract from different solvents. Antifungal assay were conducted and screened against Fusarium solani, Colletotrichum musae and two isolates of Pyricularia oryzae. Tukey post hoc test (p<0.05) was used to compare the significant difference in growth rate of fungal colony treated with different concentrations of crude extract obtained from different solvents using SPSS version 20. Antifungal assay of 27 crude extracts from nine medicinal plants against three crop pathogenic fungi were reported in this study. Out of 27 crude extracts, eight crude extracts were significantly retarding the growth of all tested crop pathogenic fungi. There were 16 crude extracts significantly retarding the growth of at least one crop pathogenic fungi while three crude extracts had no fungistatic effect on neither one of the crop pathogenic fungus. This suggested that the antifungal activity of crude extracts were fungal species dependent. Isolate dependent of growth retardation effect was observed based on the antifungal assay against isolate POSA1 and POSA2 of P. oryzae. The selective activity of crude extract with fungal dependent and isolate dependent properties may not be applicable in the field because searching for potent antifungal agent need to be effective to most significant species or isolates of crop pathogenic fungi. Mostly, the fungal growth rate was delayed by two to four days to reach the full plate compared to corresponding control plates. Crude extracts from different medicinal plant species were found to be effective in retarding but not killing the tested crop pathogenic fungi. The effectiveness of antifungal activities may be likely due to the presence of secondary metabolites in extracts of medicinal plants. Further research on the active secondary metabolites from plant extract is prominent to uncover potential antifungal agents.